Cooperative Learning and Social Development in Elementary Classroom - Jose, Sunitah Susan; Poulose, P.J. (JOURNAL OF INDIAN EDUCATION, 2011)
Cooperative learning has sufficient scope for accommodating social goals, goals that could enrich the beauty of human solidarity via celebration of multidimensional perspectives. Our society considers the elementary class as a laboratory. Use of cooperative learning in elementary classrooms helps in achieving the overall goals of education because they incorporate intellectual, social and psychological aspects of education and enhance social development. This article is an introduction to cooperative learning and its impact in social development. This also discusses the reason for using cooperative learning strategies in elementary classes.